Research note: are caring professions' students more receptive to diverse groups?. Issue 5 (3rd September 2022) - Segev, Ronen; Even-Zahav, Ronit; Neter, Efrat
ABSTRACT: Cultural competence (CC), also known as cultural intelligence (CQ), is a necessary skill for caring professions. Little is known, though, about initial levels of CQ or differences in CQ levels between students in caring and non-caring programs. A group of first-year students (n = 172) from diverse demographic backgrounds and different fields of study (social work, nursing, behavioural sciences) participated in an online survey that assessed their CQ and background attributes. Significant differences were found across fields of study so that students pursuing caring professions were more receptive than their counterparts in non-caring fields to intercultural interaction in the motivational, cognitive, and meta-cognitive CQ dimensions with no significant difference in the behavioral dimension. Mastering a non-native language was also associated with motivational and cognitive CQ. These findings suggest that greater receptiveness to intercultural interaction among students pursuing caring professions needs to be nurtured in order to generate behavioral changes.